Mechanism for efficient separation of eugenol and eugenol acetate with β-cyclodextrin as a selective solvent. Issue 12 (2nd December 2019) - Yang, Zujin; Chai, Yuxin; Zhou, Dan; Yao, Xingdong; Ji, Hongbing
ABSTRACT: Separation of active components from essential oils is very difficult due to some similar chemical and physical properties. In this work, a facile method is developed to reduce the separation cost. β -Cyclodextrin ( β -CD) is used for the separation of eugenol and eugenol acetate by forming the inclusion complexation of non-covalent host–guest interactions. The separation was achieved by a co-precipitation method, using ethanol:water (1:4, v/v) as a solvent at the temperature of 50 °C for 2 h. The molar ratio of guests to β -CD for complexation was 4:1. The inclusion rate of eugenol increased to 60% with a separation factor of 2.5, and the purity of eugenol was up to 99% from 50% after one cycle. β -CD can be easily recovered with industrial ethanol (95%, v/v) and used repeatedly. A possible mechanism is also proposed based on the experimental and computational methods. The results indicate that β -CD is suitable to separate the aromatic constituents from the natural products. Graphical abstract: Selectively separate eugenol from eugenol acetate, which was attributed to the difference of weak interactions between guests and β -CD, i.e. hydrogen bonding interaction.